(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
Cooperatives are now required to have employees who are able to show their best performance in order to survive and develop better. The purpose of this study was to determine the effect of transformational leadership on employee performance mediated by work motivation at the Bhuana Mas Jaya Savings and Loan Cooperative (KSP) in Denpasar City. The population of this study was all employees of KSP Bhuana Mas Jaya, totaling 35 people, all of whom were involved in the study. The data analysis techniques used were path analysis and the Sobel test. The results of the analysis proved that transformational leadership had a positive and insignificant effect on employee performance, transformational leadership had a positive and significant effect on work motivation, and work motivation had a positive and significant effect on employee performance. The results of the Sobel test proved that work motivation fully mediated the effect of transformational leadership on employee performance. Suggestions given include creating a culture of innovation, providing incentives to innovative employees, evaluating employee job placement, and holding discussion sessions to listen to employee aspirations